An environmentally-friendly enzyme-based nanofibrous membrane for 3, 3′, 5, 5′-tetrabromobisphenol removal1. Issue 79 (28th August 2015) - Xu, Ran; Tang, Rongzhi; Liu, Sijia; Li, Fengting; Zhang, Bingru
<x xml:space="preserve">Abstract</x> Immobilization of HRP on NCC-incorporated CS/PVA membranes and its application in TBBPA removal.